Digital cultural heritage—A challenge for the chemical engineering: Contextualizing materials in a holistic framework - Ioannides, Marinos; Alexakis, E.; Coughenour, Chance M.; Vincent, Matthew L.; Gutierrez, M. F.; Lopez-Menchero Bendicho, V. M.; Fritsch, Dieter; Moropoulou, A.; Rajcic, Vlatka; Zarnic, Roko (My University, 2015)
Materials science and chemical engineering are imperative for the preservation and conservation of cultural heritage. The integration of novel methods in cultural heritage documentation, which yields an exponential amount of data, demands rigorous academic analysis. Often times these data are not integrated into the databases that form the core of cultural heritage recording systems, and therefore are often lost when the specialists complete their work. The Initial Training Network for Digital Cultural Heritage (ITN-DCH wqww.itn-dch.eu) proposes a holistic framework for cultural heritage that integrates all the data and systems in ways that allow for contextual data retrieval. In the Troodos Mountains of Cyprus, the Byzantine church of Panagia Forviotissa Asinou (or simply Asinou), is a UNESCO World Heritage site (http://whc.unesco.org/en/list/351) and forms one of the ten monuments in the region known as the painted churches of Troodos Region (http://www.byzantinecyprus. com/). The church represents a complex set of information, from ancient inscriptions dating to the founding of the monument in the 12th century, to modern video recordings from Cypriot television broadcasts. All of this information must be presented together in a single, holistic framework that allows researchers to approach the monument as a single unit, rather than searching for this information from disparate sources in archives and repositories around the world. The authors will present the framework being developed by the ITN-DCH through the lens of one of their case studies at Asinou. This framework demonstrates the integration of all types of different information, and demonstrates how cultural heritage management can be conducted in such a way that unifies data and encourages transdisciplinary research. Future work will include applications at other project case studies, demonstrating its application at other sites in Europe.
Keywords: Preservation; Cultural heritage; Church of Panagia Forviotissa Asinou; Byzantine churches; Conservation of cultural heritages; Cultural Heritage documentations